Distribusi Penguasaan dan Pemilikan Tanah Pertanian di Desa Nglegok, Kabupaten Karanganyar - Jefri Bangkit Angkoso; Ahmad Nashih Luthfi; Sudibyanung Sudibyanung (Tunas Agraria, 2020)
Abstract: There is inequality for land tenure and land ownership in Indonesia in recent decades. The Gini Index can be used to see the level of inequality in the distribution of land tenure and land ownership. The purpose of this research is to determine the distribution of land tenure and land ownership of agricultural land, the level of inequality, and the influencing factors. This research uses qualitative methods with case study strategies. The results of this study are in Ngungkal, in the largest class of land tenure and land ownership, 13.875 m² of agricultural land is only owned by 1 farmer family (0.59% of the total sample). In the smallest class, 13.766 m² of agricultural land is owned by 126 farmer families (11.30% of the total sample). In the largest class of land tenure and land ownership in Talok, 5.532 m² of agricultural land is owned by 1 farmer family (1,89% of the total sample), while on the smallest class 7.583 m² of agricultural land is owned by 29 farmer families (22,64% of the total sample). Gini Index in land tenure and land ownership of agricultural land in Ngungkal and Talok is high, namely 0.72 in Ngungkal and 0.52 in Talok. The small size of agricultural land owned by farmer families due to land fragmentation through legal actions in the form of buying and selling and grants, as well as legal events in the form of inheritance. Fragmentation of agricultural land in Nglegok Village causes the “gurem” effect on farm families, where the size of agricultural land which is initially small becomes even smaller.Keywords: agricultural land, inequality, gini index, gurem. Intisari: Ketimpangan penguasaan dan pemilikan terjadi di Indonesia dalam beberapa dekade terakhir. Indeks Gini dapat digunakan untuk melihat tingkat ketimpangan distribusi penguasaan dan pemilikan tanah di suatu wilayah. Tujuan penelitian ini adalah untuk mengetahui distribusi penguasaan dan pemilikan tanah pertanian, tingkat ketimpangannya dan faktor yang mempengaruhinya. Penelitian ini menggunakan metode kualitatif dengan strategi studi kasus. Hasil dari penelitian ini adalah di Dusun Ngungkal, di kelas terbesar penguasaan dan pemilikan tanah, 13.875 m² lahan pertanian hanya dimiliki oleh 1 keluarga petani (0,59% dari total sampel). Di kelas terkecil, 13.766 m² tanah pertanian dimiliki oleh 126 keluarga petani (11,30% dari total sampel). Di kelas terbesar kepemilikan tanah dan kepemilikan tanah di Dusun Talok, 5.532 m² tanah pertanian dimiliki oleh 1 keluarga petani (1,89% dari total sampel), sedangkan pada kelas terkecil, tanah pertanian seluas 7.583 m² dimiliki oleh 29 keluarga petani (22,64% dari total sampel). Indeks Gini penguasaan dan pemilikan tanah pertanian di Ngungkal dan Talok tergolong tinggi, yaitu 0,72 di Ngungkal dan 0,52 di Talok. Kecilnya luas tanah pertanian yang dimiliki kepala pertani akibat adanya fragmentasi tanah melalui perbuatan hukum berupa jual beli dan hibah, serta peristiwa hukum berupa pewarisan. Fragmentasi tanah pertanian di Desa Nglegok menyebabkan efek guremisasi pada keluarga petani, dimana luas tanah pertanian yang pada awalnya sudah kecil menjadi semakin kecil lagi.Kata kunci: tanah pertanian, ketimpangan, indeks gini, gurem.